2019
DOI: 10.1002/ijc.32083
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term use of low‐dose aspirin for cancer prevention: A 10‐year population cohort study in Hong Kong

Abstract: Aspirin, commonly used for prevention of cardiovascular and cerebrovascular diseases, has been found to possess protective effects against cancer development in the Western populations. Such effects among Asian populations remain uncertain. The objective of this study is to investigate the use of aspirin on prevention of different cancers among Chinese users. This population‐based study utilized database from the Hong Kong Hospital Authority; adults with aspirin prescription for at least 6 months between 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 36 publications
4
96
0
1
Order By: Relevance
“…A total of 33 studies were included in the final analysis (Fig. ) . Characteristics of the included studies, outcomes, characteristics of the drug exposure, and study quality are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 33 studies were included in the final analysis (Fig. ) . Characteristics of the included studies, outcomes, characteristics of the drug exposure, and study quality are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
“…1). 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Characteristics of the included studies, outcomes, characteristics of the drug exposure, and study quality are provided in Table 1. A total of 1 927 971 patients were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…However, this potential does not take in account the side effects of ASA; therefore, the use of this compound as an adjuvant therapy, especially for paediatric patients, would require caution . Moreover, a very recent study, while confirming that the chronic use of ASA correlates with a reduced risk for different cancers, has shown that, unexpectedly, it could also have opposite effects, in particular by increasing the risk of breast cancer . In this light, further in vivo preclinical investigation, possibly involving human tumour xenograft of NB in nude mice, will be required, in order to confirm the efficacy of ASA and to consider a careful risk‐benefit assessment.…”
Section: Discussionmentioning
confidence: 99%
“…These two platelet-derived eicosanoids have also been shown to exert pro-malignant effects in several cancer types, by activating mitogen and angiogenic pathways [139][140][141][142]. Coherently, blockage of COX-1 by aspirin causes the loss of platelet ability to transform human colon carcinoma cells into mesenchymal-like cells [139,143] and the long-term use of low-dose aspirin is associated with a reduction in risk of various cancers [144].…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 99%